Ecotourism and Geopark: A Potential For a Sustainable Symbiosis - Muqsitul Fajar, Abdul Syahid; Maryani, Enok; Arrasyid, Riko; Moch Isya, Herdien Raka (Jurnal Pendidikan Ilmu Sosial, 2023)
This research attempts to highlight the symbiotic relationship between the conservation of geopark natural resources and the competitiveness of ecotourism destinations. While the intrinsic environmental reasons for land protection are losing their appeal due to environmental damage. This research uses descriptive method with qualitative analysis techniques. The results of this study explain that ecotourism can provide greater benefits for the quality of natural resources in an area than considering the use of natural resources based on other factors such as local economic conditions. Through ecotourism visiting sensitive areas such as geoparks, local communities can be provided with additional economic incentives to protect their natural resources that might not exist in the absence of tourism.